The effects of COVID-19 on the water sector - Ibrahim, Sarah (Frontiers in Environmental Science, 2022)
COVID-19 pandemic affected the public health, the economy, the social life and the environment. It infected and killed millions of people around the world. Most of the recent literature has focused on the medications to combat this virus, including antivirals and vaccines. But studies about its effect on the environment are still rare, particularly on the water sector. Most of the studies concentrate on the effect of water availability on COVID-19, the effect of the used medications on the water and the probability of transmission of SARS-CoV2 through water. Here we have summarized the effects of COVID-19 on the water sector, from many perspectives. We show different methods to detect the effect of the pandemic on water. Also, methods to investigate the presence of the virus or its RNA in the water. We also show the different effects of its presence in the wastewater; the probability of transmission, the detection of different variants and the prediction of new waves. We also show the disadvantages and the advantages of the pandemic on the water sector. We finally suggest some recommendations to face this pandemic and the future pandemics, for the governments and water policymakers, water treatment plants, general population, and researchers. The aim of this review is to show the different aspects of the pandemic, in order to give a general idea about what must be done in order to minimize its effect and any probable pandemic in the future.